Quasi-relativistic harmonic oscillator bound states - Mustafa, O; Odeh, M (Iop Publishing Ltd, 1999)
The quasi-relativistic harmonic oscillator bound states constructed by Znojil (1996 J. Phys. A: Math. Gen. 29 2905) are investigated via a new methodical proposal. Compared with those obtained by an anonymous referee (from a direct numerical integration method) of Znojil's paper, our results appear to be more favourable than those obtained by Znojil via quasi-perturbative, variational, Hill-determinant and Riccati-Pade methods. Bound states with larger angular momenta, l, are also constructed.
Keywords: Shifted 1/N Expansion; Magnetic-Field; Quantum-Dot; Schrodinger-Equation; Potentials; Eigenvalues